(untitled) (Biological Sciences - PJSIR, 1996)
and two macrocyclic Schiff’s bases have been synthesised and characterized by elemental analyses, conductivity measurements and infrared spectral studies. Their reactivities as potential oxygen carriers have also been studied. Complexes containing thebidentate macrocyclicligandarenonelectrolytes in DMF.The present complexes havethe compositions: [M(02)2L], [M=Zr (IV) and Th (Iv); L = 2, 6 -diaminopyridine or Schiff base derived from ethylenediamine and benzil, CI6HI6N2and Schiff base of diethylenetriamine with benzil, CI8H2IN3];[UO(O) L], [L = 2, 6-diaminopyridine or Schiffs base of diethylenetriamine and benzil, CISH21NJInfrared spectra of the com- plexes revealthat forM(02) grouping,the’\)1(0-0) stretchingmodedecreaseswiththe increaseintheatomicnumber in a group.The Zr (IV) andTh (Iv) complexes containing thebidentate neutralmacrocyclic ligand oxidise PPH3and AsPh3andthosecontaining tridentateacyclicandtridentatemacrocyclicligandsareinert towards oxidation reactions.